3D Force Sensor - Roberti, M. (2006)
Force sensors are used in industry for weighing measurements. Basically it is an elastic element to which an appropriate type of strain sensor is bounded. The application of a force to the elastic element causes a deformation sensed by the strain sensor providing an electrical output proportional to the applied force. In the present work is proposed a novel structure designed for low cost compressive force sensing. Some features of this approach are: good performance to cost ratio, robust design, long-term stability and suitable for difficult environments. Fabrication methods of different meso-scale structures using Low Temperature Cofired Ceramics (LTCC) technology and preliminary sensor characterization are also presented.